An intact immune system is required for the anticancer activities of histone deacetylase inhibitors - West, Alison C; Mattarollo, Stephen R; Shortt, Jake; Cluse, Leonie A; Christiansen, Ailsa J; Smyth, Mark J; Johnstone, Ricky W (Cancer research (Chicago, Ill.), 2013)
Cell-intrinsic effects such as induction of apoptosis and/or inhibition of cell proliferation have been proposed as the major antitumor responses to histone deacetylase inhibitors (HDACi). These compounds can also mediate immune-modulatory effects that may contribute to their anticancer effects. However, HDACi can also induce anti-inflammatory, and potentially immunosuppressive, outcomes. We therefore sought to clarify the role of the immune system in mediating the efficacy of HDACi in a physiologic setting, using preclinical, syngeneic murine models of hematologic malignancies and solid tumors. We showed an intact immune system was required for the robust anticancer effects of the HDACi vorinostat and panobinostat against a colon adenocarcinoma and two aggressive models of leukemia/lymphoma. Importantly, although HDACi-treated immunocompromised mice bearing established lymphoma succumbed to disease significantly earlier than tumor bearing, HDACi-treated wild-type (WT) mice, treatment with the conventional chemotherapeutic etoposide equivalently enhanced the survival of both strains. IFN-γ and tumor cell signaling through IFN-γR were particularly important for the anticancer effects of HDACi, and vorinostat and IFN-γ acted in concert to enhance the immunogenicity of tumor cells. Furthermore, we show that a combination of vorinostat with α-galactosylceramide (α-GalCer), an IFN-γ-inducing agent, was significantly more potent against established lymphoma than vorinostat treatment alone. Intriguingly, B cells, but not natural killer cells or CD8(+) T cells, were implicated as effectors of the vorinostat antitumor immune response. Together, our data suggest HDACi are immunostimulatory during cancer treatment and that combinatorial therapeutic regimes with immunotherapies should be considered in the clinic.